2018
DOI: 10.3389/fpsyt.2018.00695
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Depression on the Psychometric Properties of the Maslach Burnout Inventory–Human Services Survey: A Cross-Sectional Study With Nursing Assistants

Abstract: Background: The Maslach Burnout Inventory-Human Services Survey (MBI-HSS) is the most commonly used instrument to assess burnout. Although various factors have been reported to influence its validity, the influence of major depressive disorder (MDD) has not been previously considered. We developed this study to investigate the influence of MDD on the psychometric properties of the MBI-HSS in nursing assistants.Results: From a sample of 521 nursing assistants, we found in those with MDD (n = 138, 24.56%) a degr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…Another Brazilian study with a sample of nursing assistants, divided between groups with major depressive disorder and absence of the disorder, found that the acceptable rates for RMSEA and CFI occurred in the group with no disorder. And in the general sample of the study, the three-factor model proved to be acceptable, but concluding that the two-factor model was better adjusted in this sample (29) .…”
Section: Discussionmentioning
confidence: 81%
“…Another Brazilian study with a sample of nursing assistants, divided between groups with major depressive disorder and absence of the disorder, found that the acceptable rates for RMSEA and CFI occurred in the group with no disorder. And in the general sample of the study, the three-factor model proved to be acceptable, but concluding that the two-factor model was better adjusted in this sample (29) .…”
Section: Discussionmentioning
confidence: 81%
“…The perceived stress was a significantly positive predictor of EE. EE, as the most core element in the Maslach burnout model, was regarded as feelings of being emotionally drained and depleted of one's emotional resources ( 41 ). Just as Maslach et al ( 42 ) stated, “when people describe themselves as experiencing burnout, they are most often referring to the experience of emotional exhaustion”.…”
Section: Discussionmentioning
confidence: 99%
“…However, given that the current data constitute the first investigation of burnout symptoms within the context of multiple health-promoting factors across different occupations in a large sample, results should be interpreted with caution. Particularly considering that some studies identified problems with the factorial validity of the MBI scales specifically in heavily burdened populations [97,98].…”
Section: Discussionmentioning
confidence: 99%